Prediction of Epileptic Seizures using digital signal processing and support vector machine - Siddique, Nusayer Masud; Sayeed, Samee Mohammad; Ahmed, Zaziba; Ahmad, Shaikh Rezwan Rafid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.